Back to Basics: Insurance - Hungelmann, Jack (John Wiley & Sons, 2018)
Choosing insurance may br intimidating, but it doesn't have to be. The tools in Back to Basics: Insurance will empower you to make the best insurance decisions for your circumstances. In this book, you find the fundamentals of automobile, homeowner's, group health, long-term disability, and life insurance, and you get guidance on managing risk and updating your policies when your life changes. With easy-to-understand explanations and practical advice, you can protect yourself and you lowed ones with the right insurance program.